Profil Petani Sayur di Kabupaten Karanganyar Berdasarkan Kadar Kholinesterase dan Fungsi Tiroidnya - Purwandari, Rina; Musoddaq, Muhamad Arif; Fuada, Noviati (Media Penelitian dan Pengembangan Kesehatan, 2017)
Iodine is an essential mineral. This mineral is indispensable as thyroid forming substance, which is produced by the thyroid gland. The performance of the thyroid gland could be disrupted by the pesticide, when used excessively. Disorders occur in the process of thyroid hormone synthesis, which is on the receptor TSH (Thyroid Stimulating Hormone) in the thyroid gland. Thyroid hormone synthesis become inhibited because TSH can not enter the thyroid gland. It also inhibits the work of enzymes that act as catalyst for changes in T4 and T3 (active forms of hormones in the body). The presence of pesticides in the body is indicated by levels of cholinesterase in the blood. This study was conducted to know the profile of farmers exposed to pesticides, measure levels of cholinestrase (CHE), TSH levels in the blood of farmers, and analyze the relationship of pesticide residues (blood cholinestrase levels) to thyroid function (TSH level). Subject of research (N) was 109 farmers. Characteristic data were obtained by interview using structured instruments. Levels of TSH and T4 were analyzed by ELISA method. Cholinesterase was measured by spectrophotometry. Test kit was used to test the quality of salt. The results of this study showed 7.3% of farmers have cholinesterase levels below normal limits; 4.6% of farmers have high levels of TSH; and 6.4% of farmers have T4 levels below normal values. It is concluded that farmers with subclinical hypothyroidism and low-levels of poisoning are still found. However, there is no relationship between pesticide residues and thyroid function in farmers. Â  Abstrak Iodium merupakan mineral esensial. Mineral tersebut sangat diperlukan sebagai zat pembentuk hormon tiroid yang diproduksi oleh kelenjar tiroid. Kinerja kelenjar tiroid dapat terganggu oleh pestisida apabila digunakan secara berlebihan. Gangguan terjadi pada proses sintesis hormon tiroid, yaitu pada reseptor TSH (Thyroid Stimulating Hormone) di kelenjar tiroid. Sintesis hormon tiroid menjadi terhambat karena TSH tidak dapat masuk ke kelenjar tiroid. Menghambat pula kerja enzim yang berfungsi sebagai katalis perubahan T4 dan T3 (bentuk aktif hormon dalam tubuh). Keberadaan pestisida dalam tubuh diindikasikan dengan kadar kholinesterase dalam darah. Tujuan penelitian untuk mengetahui profil petani yang terpapar pestisida, mengukur kadar kholinestrase (CHE), kadar TSH dalam darah petani, dan menganalisis hubungan residu pestisida (kadar kholinestrase darah) terhadap fungsi tiroid (kadar TSH). Subyek penelitian (N) sebesar 109 petani. Data karakteristik diperoleh dengan wawancara menggunakan instrumen terstruktur. Kadar TSH dan T4 dianalisis dengan metode ELISA. Kholinesterase diukur dengan spektrofotometri. Tes kit untuk menguji kualitas garam. Hasil penelitian menunjukkan sebesar 7,3% petani memiliki kadar kholinesterase di bawah batas normal; 4,6% petani memiliki kadar TSH tinggi; dan 6,4% petani memiliki kadar T4 di bawah nilai normal. Tidak terdapat hubungan antara residu pestisida dengan fungsi tiroid pada petani. Kesimpulan penelitian adalah petani yang mengalami hipotiroid subklinis dan keracunan tingkat rendah masih ditemukan. Namun demikian tidak terdapat hubungan antara residu pestisida dengan fungsi tiroid pada petani.